The Current Clinical Trial Landscape for Hidradenitis Suppurativa: A Narrative Review - Amanda Hunt; Victoria Qian; Hailey Olds; Steven Daveluy (Adis, Springer Healthcare, 2023)
Abstract Hidradenitis suppurativa (HS) is a skin disease resulting from chronic, recurrent inflammation around hair follicles, characterized by proinflammatory cytokines such as IL-1, IL-17, IL-23, and TNF-α. While adalimumab, a TNF-α targeting human IgG monoclonal antibody, is the only approved treatment for HS, there are many other therapies being investigated now targeting other key players in inflammatory pathways such as the cytokines listed above, C5a in the complement pathway, and Janus kinase (JAK). This review discusses current clinical trials for biologics and small molecules, procedures, and wound dressings undergoing study in hidradenitis suppurativa.